Late Isometric Assessment of Hip Abductor Muscle and Its Relationship with Functional Tests in Elderly Women Undergoing Replacement of Unilateral Hip Joint. (October 2015) - Melchiorri, Giovanni; Viero, Valerio; Triossi, Tamara; Sorge, Roberto; Marchetti, Chiara; Arena, Nicola Eugenio; Tancredi, Virginia
ABSTRACT: Objective: The aim of this study was to evaluate the recovery of muscle strength and measure autonomy 3 yrs after hip replacement surgery in a sample of patients. Design: Seventy-eight female patients (70.7 ± 6.3 yrs old) operated on for hip replacement were evaluated. They underwent evaluation tests for hip abductor muscle strength on the healthy and operated limb using strength curves obtained with isometric assessments. Autonomy was evaluated with a rating scale Western Ontario and McMaster Universities Arthritis Index (WOMAC), Harris and MOS 36-Item Short-Form Health Survey (SF-36) and functional assessment (Timed "Up and Go" test). Results: Three years after surgery, a muscle strength deficit was still noticeable on the operated limb compared with the healthy limb ranging from 9% at 5 degrees of adduction to 12% at 0 degree of abduction. The strength curves obtained on the operated side maintained the same descending trend as the healthy side. The authors found no significant correlations between the patient-reported functional measures and the hip abductor strength deficit. The Timed Up and Go test was moderately correlated with the muscle strength deficit. The association between the deficit and the Timed Up and Go test was statistically significant. Conclusions: The evaluation of muscle strength and functional tests are more useful than the rating scales in patients 3 yrs after surgery. The strength curves are useful to have different levels of information and describe joint function.